Virtual Training System for Hydraulic Pump Cart Based on Virtual Reality - Wusha Huang; Qiang Chen; Minzhuo Wang; Haonan Ye (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper dissertates the application of Virtual Reality Technology in the training process. Virtual training system has more advantages than traditional training system. The design of virtual training system based on PTC DIVISION Mockup software, position tracker and 3-D mouse is proposed. The system is divided into two parts: directing part and operating part. Collision detection is discussed to improve the sense of reality in the virtual environment .This system is applied to the training process of hydraulic pump cart’s assembly and disassembly. More immersive training effect is obtained in this system. The goal of reducing training costs and improving the efficiency of training can be achieved in the virtual training system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3026